INTRADIALYSIS HYPOTENSION: CAUSES, METHODSOFPREVENTION AND WAYS OF CORRECTION - I. Mogilnik (Ukrainian Journal of Nephrology and Dialysis, 2015)
There is a marked increase in the number of patients with chronic kidney disease worldwide. In Ukraine in 2013 its prevalence was 1026,3per 100000population. 7214 patients in total have received a renal replacement therapy; 74% of them had hemodialysis. Statistically, almost 90% of patients on hemodialysis were of a working age. Despite the continuous improvement of the dialysis technologies, mortality among patients remains significantly higher than in general population. In Ukraine, the mortality rate for patients on hemodialysis in 2013 was 8,2%, where cardiovascular complications were the cause ofdeath in 60,5%. Intradialysis episodes of hypotension can lead to myocardial ischemia and vascular thrombosis, which, in turn, are reducing the quality of life and life expectancy, and are significant risk factors for the death. The article describes most common causes, methods of prevention and ways of correction of the most known complications of hemodialysis.